The Exchange Rate Regime, a determinant of the degree of Risk Sharing between Profits and Wages - Arespa-Castelló, Marta (Elsevier, 2024)
The interaction between economic growth, profits, and wages at the macroeconomic level provides insights into firms' ability to manage risk and the degree of competition in the goods market. In both instances, policymakers have room to improve the institutions within the economy. We conduct a panel data analysis for 20 OECD countries and demonstrate that an increase in profits has a negative effect on wage changes, once labour market rigidities and the business cycle are controlled for. Notably, economic growth has significantly different effects on wages depending on the exchange rate regime and the phase of the business cycle. In other words, the exchange rate regime is an important determinant of the extent to which economic growth translates into wage changes: when a country operates with a flexible exchange rate, wages absorb a greater share of GDP (Gross Domestic Product) fluctuations over the business cycle, thereby sharing risk with capital owners. The strength of democracy and the rigidity of labour market legislation also play a crucial role in wage variations.
Keywords: Macroeconomía; Risk sharing; Profits and wages; Exchange rate regime; Business cycle; Macroeconomic panel data